IMPLEMENTASI PEMBIAYAAN PADA PRODUK ARRUM PT. PEGADAIAN SYARIAH CABANG SINGKAWANG - Sumar’in Sumar’in (Cross-border, 2021)
Shari'ah pawnshops are a form of development as well as a form of shari'ah unit of the Indonesian pawnshop. One of the financing products that are not very popular in the community is the Ar-rum product. Ar-Rum products are present in accordance with the nature of the needs of small traders who need a fast and easy source of financing. This research is in the form of descriptive research, to describe how the financing mechanism for Ar-Rum products at PT. Pegadaian Syariah Singkawang Branch. The results of this study are that the implementation of the financing process on Ar-Rum products includes in-depth interviews with prospective customers, data collection related to financing applications. aspects analyzed in this pawn include Character (character), Capacity (capacity) Capital (capital), Condition (condition), Collatera (collateral).